A Dialogue between Global Trade Governance and International Environmental and Tax Policies - Lucas Garín, Andrea (2019)
The starting point of this paper is based on the interrelation between the political and legal elements that make up and sustain the global trade governance, understanding that it is linked to environmental law and tax law. These subjects are linked each other with the international trade and, at the same time, they are interlinked through the international trade. Our purpose is to determine the dialogues that emerge from these relationships.